Study on the Analysis of Hilal Calc 3.0 Application in Determining the Beginning of the Kamariah Month - Zar'ah, Nur Fajriani; Irfan (AL - AFAQ : Jurnal Ilmu Falak dan Astronomi, 2024)
This study was motivated by the researcher's attention to the many applications used in determining the beginning of the Kamariah month. One such application that is easy to use is Hilal Calc 3.0.  The Hilal Calc 3.0 application can calculate the beginning of the Kamariah month using the hilal visibility criteria, which is relatively old. Therefore, the focus of this research is to assess the accuracy and feasibility of using this application. The research adopts a descriptive evaluative approach in the field. The results of this study indicate that the Hilal Calc 3.0 application is relatively accurate. This is supported by the calculations using the Hilal Calc 3.0 application, which show small differences compared to the Ephemeris system hisab hakiki. The largest difference between the two method is found in the calculation of the beginning of the month of Ramadan 1443 H, with an elongation difference of 0° 4'57.54".Such differences in results can occur due to human error or technical issues.